2023
DOI: 10.3390/rs15102494
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Prediction of Soil Organic Carbon Stock in the Moroccan High Atlas Using Machine Learning

Abstract: Soil organic carbon (SOC) is an essential component, which soil quality depends on. Thus, understanding the spatial distribution and controlling factors of SOC is paramount to achieving sustainable soil management. In this study, SOC prediction for the Ourika watershed in Morocco was done using four machine learning (ML) algorithms: Cubist, random forest (RF), support vector machine (SVM), and gradient boosting machine (GBM). A total of 420 soil samples were collected at three different depths (0–10 cm, 10–20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Recently, Machine learning regression has become extremely important in biomass and carbon stock estimation and has proved its efficiency in modeling trees and soil carbon stock and its spatialization [41,42]. These techniques can be used to assess and analyze the contribution of various factors (Climatic, Edaphic, Topographical.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Machine learning regression has become extremely important in biomass and carbon stock estimation and has proved its efficiency in modeling trees and soil carbon stock and its spatialization [41,42]. These techniques can be used to assess and analyze the contribution of various factors (Climatic, Edaphic, Topographical.…”
Section: Introductionmentioning
confidence: 99%
“…The study employed the RF algorithm and compared it with the Ordinary Kriging (OK) interpolation model. Meliho et al (2023) used four ML algorithms to predict SOC stock (SOCS) in the Ourika Basin of Morocco: Cubist, RF, SVM, and Gradient Boosting Mechanism (GBM). The results showed that Cubist (R² = 0.86, RMSE = 11.62 t/ha) and RF (R² = 0.79, RMSE = 13.26 t/ha) had the highest predictive ability for SOCS…”
Section: Introductionmentioning
confidence: 99%